Degradation of Ni-YSZ Electrodes in Solid Oxide Cells: Impact of Polarization and Initial Microstructure on the Ni Evolution. Issue 15 (18th November 2019) - Monaco, F.; Hubert, M.; Vulliet, J.; Ouweltjes, J. P.; Montinaro, D.; Cloetens, P.; Piccardo, P.; Lefebvre-Joud, F.; Laurencin, J.
Abstract : Two types of solid oxide cells with different Ni-YSZ cermet microstructures have been aged in electrolysis and fuel cell modes for operating times ranging from 1000 to 15000 hours. The pristine and aged cermets have been reconstructed by synchrotron X-ray holotomography. Nickel agglomeration has been observed in the bulk of the operated samples inducing a significant loss of triple phase boundary lengths. The inspection of the microstructural properties has confirmed the stabilizing role of YSZ on Ni coarsening. Furthermore, the gradients of properties quantified at the electrolyte interface have revealed a depletion of Ni only in the electrochemically active region of the electrode. The process is strongly promoted for a coarse cermet microstructure when operated under electrolysis current. The evolution of the microstructural properties has been implemented in an in-house multiscale model. The simulations have shown that the loss of performance is dominated by the depletion of Ni in case of a coarse microstructure. Thanks to the computations, it has been shown that the Ni depletion is controlled by the cathodic overpotential. To explain this dependency, it has been proposed that the accumulation of oxygen vacancies in the double layer could deteriorate the Ni/YSZ interface and trigger the Ni depletion.